Increasing Student Interest in Learning Al-Qur'an Hadith With Strategy Index Card Match - Fery Irianto Setyo Wibowo (Cigarskruie: Journal of Educational and Islamic Research, 2024)
This study aims to determine the increase in student interest in learning Al-Qur’an Hadith with the Index Card Match strategy. This research is a class action research but packaged simply. Data collection techniques with observation and interviews. The data that has been collected is analyzed with qualitative descriptive techniques with percentages. The research subjects were students of class X IPA MA Ibnul Qoyyim Putra Yogyakarta and Al-Qur’an Hadith Teacher. The results showed an increase in students' interest in learning the Qur'an Hadith with an average of 76% which was carried out using the IndexCard Match strategy, from cycle I to cycle II it can be concluded that there are positive changes from each cycle. This is evident from the value obtained before the action obtained an average of alternative "Yes" amounting to 42%. Being in the interval 40% -55% is classified as not good. In cycle I, the alternative answer "Yes" obtained an average of 56% is in the interval 40% -56% classified as not good. Whereas in cycle II there was an increase, namely the alternative answer "Yes" obtained an average of 76%, which was in the interval 76% -100% which was classified as very good.